ANTIHYPERLIPIDEMIC ACTIVITY OF ECLIPTA ALBA IN HIGH FAT DIET-INDUCED HYPERLIPIDEMIC ALBINO RATS - NAIK K, SATHEESH; M, GURUSHANTHAIAH; RAJU G, NAGESH; S, LOKANADHAM; REDDY V, SESHADRI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective is to study the antihyperlipidemic activity of Eclipta alba in hyperlipidemic albino rats and the use of herbal plants and their parts such as seeds, berries, leaves, roots, barks, or flowers for the development of drugs for therapeutic purposes which have an effective role in recent years. Methods: A total of 30 adult albino rats of Wistar strain weighing 165–215 g were utilized. Animals were treated with high fat diet for 8 weeks followed by post-treatment of E. alba for 1 week, 2 weeks, and 3 weeks, respectively. After 12 h of fasting on the last day of experiment, serum blood samples were collected in EDTA vials and processed for biochemical analysis. Results: A significant decrease in levels of total cholesterol and triglycerides was noted on animals treated with E. alba compared to high fat diet animals. Treatment of hypercholesterolemic rats with E. alba showed a marked decrease of serum low-density lipoprotein (LDL) and very LDL-cholesterol concentrations compared to the hypercholesterolemic rats. High fat diet feeding worsened the levels of serum glutamic oxaloacetic transaminase, serum glutamic pyruvic transaminase, and alkaline phosphatase enzymes, whereas the same markers were significantly improved by supplementation with E. alba compared to normal group. Conclusion: E. alba acts as antihyperlipidemic agent in hyperlipidemic conditions and helps for better health.